Multiple Parenchymal Neurocysticercosis: A Case Report - KC, I; Rana, KJ; Joshi, R; Mandal, A; Bhhatarai, S (Medical Journal of Shree Birendra Hospital, 2012)
Cysticercosis is a parasitic infection with CNS involvement in 60-90% of infested patients. The larval form of pork intestinal tapeworm (Taenia solium) is responsible for cysticercosis. Humans are the definitive hosts and usually harbor the adult tapeworm in small intestine as an asymptomatic infestation. Neurocysticercosis most commonly affects the brain parenchyma. Solitary and multiple cysts in brain parencyma is common but we came across a 24 year old lady patient with huge number of cysts which is relatively rare. The aim of this article is to report the rare case. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6450 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 44-45